Concept of Dharma in Shashi Tharoor’s Novel show business (1991) - Samrajya Lakshmi .D (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Dharma is the total cosmic responsibility, including gods, a universal justice for more inclusive, wider and profounder than any western equivalent, such as duty. What is Dharma? This is the question that Shashi Tharoor explores repeatedly in his novel; though the situations, settings and characters are sufficiently varied each time to make quests dissimilar. His preoccupations are essentially abstract. The choice that a man has to make to remain true to himself, the corrosion of values in a world that puts premium on material success, the human price of ambition in a competitive society, and the possibility of making an authentic decision in a set up where an individual is allowed very little freedom-these are the recurrent concerns running through his novel – Show Business. Shashi Tharoor shows his socio-Moral vision and mourns for the lack of Dharma in modern times. In a Post Modernistic world, where all moral values are gone with the wind, there are very few committed artists with the philosophic vision, who can wage a strong war against the advent of basic human values. Tharoor considers his art as a medium through which he tries to resurrect the lost dignity of the human being. Art therefore seems to turn into a didactic weapon by which he reinstates the lost glory of the world.